Improving Comparative Effectiveness Research of Complex Health Interventions: Standards from the Patient-Centered Outcomes Research Institute (PCORI) - Esmail, Laura C. (J Gen Intern Med, 2020)
INTRODUCTION: Complex health interventions (CHIs) are increasingly studied in comparative effectiveness research (CER), and there is a need for improvements in CHI research practices. The Patient-Centered Outcomes Research Institute (PCORI) Methodology Committee (MC) launched an effort in 2016 to develop formal guidance on this topic. OBJECTIVE: To develop a set of minimal standards for scientifically valid, transparent, and reproducible CER studies of CHIs. The standards are intended to apply to research examining a broad range of healthcare interventions including delivery system, behavior change, and other non-pharmacological interventions. METHODS: We conducted a literature review, reviewed existing methods guidance, and developed standards through an iterative process involving the MC, two panels of external research methods experts, and a 60-day public comment period. The final standards were approved by the PCORI MC and adopted by the PCORI Board of Governors on April 30, 2018. RESULTS: The final standards include the following: (1) fully describe the intervention and comparator and define their core functions, (2) specify the hypothesized causal pathways and their theoretical basis, (3) specify how adaptations to the form of the intervention and comparator will be allowed and recorded, (4) plan and describe a process evaluation, and (5) select patient outcomes informed by the causal pathway. DISCUSSION: The new standards offer three major contributions to research: (1) they provide a simple framework to help investigators address the major methodological features of a CHI study, (2) they emphasize the importance of the causal model and the need to understand how a CHI achieves its effects rather than simply measuring these effects, and (3) they require description of a CHI using the concepts of core functions and forms. While these standards apply formally to PCORI-funded CER studies, they have broad applicability. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-020-06093-6) contains supplementary material, which is available to authorized users.